Safety of FLT3 inhibitors in patients with acute myeloid leukemia. Issue 9 (2nd September 2021) - Cerchione, Claudio; Peleteiro Raíndo, Andrés; Mosquera Orgueira, Adrián; Mosquera Torre, Alicia; Bao Pérez, Laura; Marconi, Giovanni; Isidori, Alessandro; Pérez Encinas, Manuel Mateo; Martinelli, Giovanni
ABSTRACT: Introduction: Acute myeloblastic leukemia (AML) is the most frequent type of acute leukemia in adults with an incidence of 4.2 cases per 100, 000 inhabitants and poor 5-year survival. Patients with mutations in the FMS-like tyrosine kinase 3 ( FLT3) gene have poor survival and higher relapse rates compared with wild-type cases. Areas covered: Several FLT3 inhibitors have been proved in FLT3 mut AML patients, with differences in their pharmacokinetics, kinase inhibitory and adverse events profiles. First-generation multi-kinase inhibitors (midostaurin, sorafenib, lestaurtinib) target multiple proteins, whereassecond-generation inhibitors (crenolanib, quizartinib, gilteritinib) are more specific and potent inhibitors of FLT3, so they are associated with less off-target toxic effects. All of these drugs have primary and acquired mechanisms of resistance, and therefore their combinations with other drugs (checkpoint inhibitors, hypomethylating agents, standard chemotherapy) and its application in different clinical settings are under study. Expert opinion: The recent clinical development of various FLT3 inhibitors for the treatment of FLT3 mut AML is an effective therapeutic strategy. However, there are unique toxicities and drug–drug interactions that need to be resolved. It is necessary to understand the mechanisms of toxicity in order to recognize and manage them adequately.